Does educational aspect solve immigration problems in France? - Anatolevich Khokhlov, Alexander (2021)
International immigration with different reasons such as education and citizenship is by no means a new phenomenon in the modern global world. Nevertheless, intense immigration was sparked and had serious implications, especially for European countries like France after the year 2010, which marked the start of the revolution in Tunisia and the birth of such a phenomenon as the Arab spring. After the end of the colonial era and the loss of colonial possessions by France, the French state encountered the problem of the influx of an infinite number of Arab and African immigrants who had considerable ethnic, religious and cultural-historical characteristics. Exacerbating the problem was that the distinctions seemed essential even when compared with immigrants from other countries, for example, Eastern and Southern Europe. The latter had a relatively similar culture and mentality to the French, and what is the main – a common Christian value matrix. As such, they did not become a problem for the governmental policy of integrating into the cultural space of the host country. European immigrants easily sipped republican values, legal norms, traditions and customs, while making a break with their tradition of the past. However, the growth of immigrant population belonging to a different culture and religious heritage led to the fact that the strategy of the French state in this direction began to become ineffective. It is obvious that the old mechanisms of adaptation, such as obtaining French citizenship and education, do not solve emerging problems, but only generate new ones. As a result, a mutual rejection of the indigenous population and the newcomers intensified, stimulating a buildup of tension in society. As a result, this gradually turned into a matter of preserving national identity for the former, while into a matter of ensuring the survival of themselves and their children for the latter.